2016
DOI: 10.1186/s13068-016-0601-3
|View full text |Cite
|
Sign up to set email alerts
|

The dual effect of a ferredoxin-hydrogenase fusion protein in vivo: successful divergence of the photosynthetic electron flux towards hydrogen production and elevated oxygen tolerance

Abstract: BackgroundHydrogen photo-production in green algae, catalyzed by the enzyme [FeFe]-hydrogenase (HydA), is considered a promising source of renewable clean energy. Yet, a significant increase in hydrogen production efficiency is necessary for industrial scale-up. We have previously shown that a major challenge to be resolved is the inferior competitiveness of HydA with NADPH production, catalyzed by ferredoxin-NADP+-reductase (FNR). In this work, we explored the in vivo hydrogen production efficiency of Fd-HydA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
58
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(60 citation statements)
references
References 32 publications
2
58
0
Order By: Relevance
“…4b). This yielded 2.5-fold higher hydrogen productivities in the presence of competing FNR and NADP + in vitro (Yacoby et al 2011) and also showed 4.5-fold increased hydrogenase activity in vivo (Eilenberg et al 2016). In a similar manner, fusing ferredoxin with the first cytochrome P450 of the dhurrin biosynthetic pathway, CYP79A1 (Fig.…”
Section: How Can We Improve Coupling To Photosynthetic Electron Transmentioning
confidence: 76%
See 2 more Smart Citations
“…4b). This yielded 2.5-fold higher hydrogen productivities in the presence of competing FNR and NADP + in vitro (Yacoby et al 2011) and also showed 4.5-fold increased hydrogenase activity in vivo (Eilenberg et al 2016). In a similar manner, fusing ferredoxin with the first cytochrome P450 of the dhurrin biosynthetic pathway, CYP79A1 (Fig.…”
Section: How Can We Improve Coupling To Photosynthetic Electron Transmentioning
confidence: 76%
“…These hydrogenases fall into two classes, containing [Fe-Fe] (algal) or [Ni-Fe] (cyanobacterial) redox centers. Different strategies have been employed to address O 2 inhibition of hydrogenase activity and improve their competitiveness towards reduced ferredoxin, ranging from gene fusion with ferredoxin to reconfigure the iron-sulfur clusters, to conversion of a hydrogen-consuming uptake hydrogenase into a hydrogen-generating one (Yacoby et al 2011;Dubini and Ghirardi 2014;Eilenberg et al 2016;Raleiras et al 2016). …”
Section: Metabolic Engineering By Coupling Enzyme Activity To Photosymentioning
confidence: 99%
See 1 more Smart Citation
“…To make effective O 2 ‐tolerant hydrogenases, operations on the O 2 diffusion channels to the active site may be considered (Liebgott et al, ). Alternatively, other engineering strategies, such as chemical treatment (Rodríguez‐Maciá et al, ), silicification‐induced cell aggregation (Xiong et al, ), hydrogel protection (Plumeré et al, ), and protein fusion (Eilenberg et al, ) have been successfully adopted to protect hydrogenases from O 2 ‐driven damage. Both site‐directed and random mutagenesis studies have been done to improve O 2 tolerance of the enzyme (Bingham, Smith, & Swartz, ; Ghirardi, ).…”
Section: Introductionmentioning
confidence: 99%
“…Both site‐directed and random mutagenesis studies have been done to improve O 2 tolerance of the enzyme (Bingham, Smith, & Swartz, ; Ghirardi, ). By the development of high‐throughput screening methods (Wecker & Ghirardi, ; Wecker, Meuser, Posewitz, & Ghirardi, ) including those based on the cell‐free technology (Koo et al, ; Koo, Schnabel, Liong, Evitt, & Swartz, ), [FeFe] hydrogenase variants with improved O 2 tolerance have been achieved (Bingham et al, ; Eilenberg et al, ; Koo & Swartz, ). Even so, this limited success is still not sufficient for practical applications, inviting future efforts towards further improving O 2 tolerance of the enzyme.…”
Section: Introductionmentioning
confidence: 99%